Relationship between airway dysbiosis, inflammation and lung function in adults with cystic fibrosis - Frey, Dario; Boutin, Sébastien; Dittrich, A. Susanne; Gräber, Simon Y.; Stahl, Mirjam; Wege, Sabine; Herth, Felix; Sommerburg, Olaf; Schultz, Carsten; Mall, Marcus A.; Dalpke, Alexander (Journal of cystic fibrosis, 2021)
Airway dysbiosis has been associated with lung disease severity in patients with cystic fibrosis (CF). However, the relationship between dysbiosis, airway inflammation and lung function impairement remains poorly understood. The aim of this study was therefore to determine how the structure of the sputum microbiota, airway inflammation markers and spirometry are related in patients with CF. Sputum samples were collected from 106 CF patients between 12 and 72 years. These were analyzed by 16S rRNA gene amplicon sequencing. Moreover, levels of pro-inflammatory cytokines (IL-1β, IL-8, IL-6 and TNF-α) and Neutrophil elastase (NE) were determined. The relationship between the microbiota, inflammation markers and forced expiratory volume in one second percent predicted (FEV1% predicted) was evaluated by multi-parameter analysis. The microbiota α-diversity correlated inverse with inflammation markers IL-1β, IL-8, TNF-α, NE and positively with FEV1% predicted. Patients could be divided into 7 clusters based on their microbiota structure. The most diverse cluster was defined by oropharyngeal-like flora (OF) while the others were characterized by the dominance of a single pathogen. Patients with the diverse OF microbiota cluster had lower sputum inflammatory markers and higher FEV1% predicted compared to patients with a pathogen-dominated microbiota including Pseudomonas aeruginosa. Our results suggest that the diversity of the airway microbiota is an important biomarker of the severity of airway inflammation linking dysbiosis to lung function decline in patients with CF.